A Comprehensive Review for Swab and Surge Pressures in Oil Wells - Assi, Amel Habeeb (Basrah Journal for Engineering Sciences, 2024)
Surge pressure is the additional pressure created when pipes move downward, and swab pressure is the pressure reduction that occurs when pipes move upward. When pipes are raised, it can result in a decrease in the pressure at the bottom of the hole due to the influence of pressure. An investigation showed that surge pressure is important for the circulation loss problem produced by unstable processes in Management Pressure Drilling (MPD) actions. Trip margin is an increase of mud density for providing overbalance so as to recompense the swabbing effect through pulling out the pipes of hole. Through trip margin there is an increase in the hydrostatic pressure of mud that compensates for the reduction of bottom pressure due to stop pumping and/or swabbing effect while pulling pipe out of hole. This overview shows suggested mathematical/numerical models for simulating surge pressure problem inside the wellbore with adjustable cross-section parts. To run the analyzed models, input data such as fluid speed around the drill pipe, pipe movement speed, hole diameter, drill pipe diameter, and internal drill pipe diameter are required. These data can be obtained from the drilling rig website. Swab pressures and surge pressures have been the primary causes of wellbore instability and blowouts in the oil industry for many years, resulting in pressure changes. This review focused on the most important basic theories for calculating the optimal factors related to surge and swab pressures and then linking them to the most important programs for calculating them. One of the most important conclusions from this review is that the optimal speed must be determined for the lowering and raising of pipes, to prevent kick or losses.